PERLAWANAN INDIA TERHADAP DOMINASI INGGRIS YANG TERGAMBAR PADA CERPEN ANY OTHER NAME KARYA SANTHA RAMA RAU - Syam, Essy (Universitas Lancang Kuning, 2014)
A short story By Any Other Name written by Santha Rama Rau deals with British domination over the Indians. The story tells abot Indian children who study in Anglo-Indian school, a non-boarding school with British administrators. The British headmaster of the school shows the British domination by using her power to change the names of the Indian students only because it’s hard for her to pronounce Indians’ names. Besides, Indians are labelled with negative stereotype. Indians are considered dishonest. For that reason, they are not trusted in a test and consequently are seated with a desk between each one to avoid cheating. To respond those unfair and discriminative treatments, Indians resist and oppose. Their resistance and opposition are reflected by their refusal to stay in that school and their decision to quit.